Des forêts mélangées, une stratégie pour produire du bois face aux enjeux énergétiques et climatiques ? Mixing tree species: a strategy to face energy and climate issues? - PEROT, Thomas ; VALLET, Patrick (Sciences, Eaux & Territoires, 2012)
Garantir une offre en bois suffisante sans nuire à l'équilibre des écosystèmes dans un contexte de changement climatique est un des principaux objectifs visés par les recherches en gestion forestière. Le mélange d'espèces d'arbre au sein d'un peuplement forestier est une stratégie qui peut répondre à ces nouveaux enjeux. À Irstea, des travaux sont déjà engagés pour améliorer les connaissances sur le fonctionnement des écosystèmes forestiers mélangés et proposer des modes de gestion adaptés aux différents types d’assemblage d’espèces. Mixing tree species is a strategy that may have several advantages in terms of wood productivity. This strategy may have a positive effect on productivity and could limit the consequences of the weakening or disappearance of a species because of climate change. Nevertheless, the link between productivity and mixture is a hard topic and depends on a combination of factors that vary in space and time. Using data from the National Forest Inventory and long-term experiments are two complementary approaches to improve our knowledge on the functioning of mixed forests and to be able to define management strategies adapted to the different kinds of species assemblages and for different climatic conditions.